Development of a comic interactive-based problem-based learning model to improve the critical thinking skills of elementary students - Amrin, Amrin; Mochammad Noeryoko; Muh. Ma’ruf; Khaerunnisa, Khaerunnisa; M. Ibnusaputra; Ibrahim Pandu Ame (Jurnal Inovasi Teknologi Pendidikan, 2026)
The era of the Industrial Revolution 5.0 requires the education sector to adapt to rapid technological developments, particularly through the adoption of innovative learning models. This study aims to develop a feasible, practical, and effective comic-based interactive Problem-Based Learning (PBL) model to improve elementary school students' critical thinking skills. The method used is research and development (R&D) with the ADDIE model, involving a qualitative approach to assess the product's feasibility and practicality, and a quantitative approach to measure its effectiveness through a pretest-posttest design. The research subjects were 30 fifth-grade students at Elementary School 9 Sila, Bima Regency. The instruments used included a feasibility questionnaire, a practicality questionnaire, and a critical thinking skills test. The results showed that the products developed for the PBL model (90.8%), interactive comics (96.5%), and critical thinking skills tests (95.7%) were feasible for use. The practicality level of interactive comics (93.25%) and critical thinking skills tests (97.75%) was very practical for use in elementary school learning. The n-Gain test results showed an increase in critical thinking skills with an average score of 0.74 (high category). This was supported by a significant paired-samples t-test (p < 0.05), which showed a difference between the students' pretest and posttest scores. In general, these results indicate that the application of the comic interactive-based PBL model is effective in improving students' critical thinking skills.